The Legal Vacuum in Bankruptcy Resolution Based on Sharia Contracts - Syahputra, M Arif; Arief Fakrulloh, Zudan (Asian Journal of Social and Humanities, 2024)
This research addresses the legal vacuum concerning the bankruptcy of sharia financial institutions in Indonesia, arising from the incompatibility between Law No. 37 of 2004 on Bankruptcy and Law No. 3 of 2006, which grants authority to Religious Courts in resolving sharia economic disputes. The unique operational principles of sharia financial institutions are not adequately accommodated within the current legal framework, leading to legal uncertainty, procedural challenges, and risks to public trust. This study aims to identify these legal gaps, analyze their implications, and propose solutions to ensure legal certainty and justice. Using a normative juridical method, the research focuses on analyzing relevant laws, legal doctrines, and fatwas issued by the Indonesian Ulema Council (MUI) while conducting a comparative study of best practices in other jurisdictions. The findings reveal that the absence of specific regulations, limited technical capacity of Religious Courts, and insufficient legal literacy among stakeholders exacerbate the problem. To address this, the research proposes the creation of specific regulations tailored to sharia bankruptcies, the enhancement of Religious Court capacities, stakeholder education, and the active role of MUI in issuing fatwas as legal guidelines. These measures are expected to foster legal certainty, procedural fairness, and public trust in the sharia finance sector while ensuring a just and efficient dispute resolution system.